#TITLE_ALTERNATIVE# - ANGGI ANDINI (NIM 29110002) ; Pembimbing : Prof. Togar M. Simatupang, RAHAJENG
Delivery in Full on Time Accurate Invoice (DIFOTAI) is the most important KPI in Coca-Cola Bottling Indonesia (CCBI) in fulfilling market demand. The target for DIFOTAI 2011 was 96% and 2011 performance was below the target. There were several problems that cause this; one of them is West Java Minute Maid Pulpy products inventory plan performance. Demand and supply actual data during October Ã‚Â– November 2011 was used to modeling existing system. Root cause analysis showed that root causes of this symptom were: inventory level in plant only considering demand from DC, slow response in replenishment process, and negative impact from low forecast accuracy. Variations of possible solutions generated 19 possible solution scenarios. Target performance measures were determined to measure the performance of each scenario. These scenarios then simulated using Monte Carlo simulation with forecast, demand from other operations, and purchase order as random variables based on probability in actual data. Simulation result showed that the most optimal performance were: using 3.5 days in coverage as target LOI in plant based on daily demand from DC and daily demand from other operations, MPS update based on ending inventory at DC one time a week, and using Ã‚Â„predicted ending inventory‟ to reduce replenishment process.